Effect of type D personality on smoking status and their combined impact on outcome after acute myocardial infarction. Issue 3 (19th February 2018) - Imbalzano, Egidio; Vatrano, Marco; Quartuccio, Sebastiano; Ceravolo, Roberto; Ciconte, Vincenzo Antonio; Rotella, Paola; Pardeo, Renato; Trapani, Giovanni; De Fazio, Pasquale; Segura‐Garcia, Cristina; Costantino, Rossella; Saitta, Antonino; et al.
Abstract : Background: Smoking cessation is correlated with several psychological, social, biological, and pharmacological aspects. The combined tendency to experience negative emotions and to inhibit the expression of these emotions is indicated as "type D personality, " an independent risk marker for clinical outcome in cardiac disease. Despite this effect of type D personality on cardiovascular disease, it is still unclear whether this personality trait may influence smoking cessation after a myocardial infarction. Hypothesis: we hypothesized that there is a relationship between type D personality and smoking persistence in acute coronary syndrome patients, and this association may predict a worse long‐term prognosis. Methods: The study enrolled 231 patients with ST‐segment elevation myocardial infarction, treated with primary percutaneous coronary intervention. Type D scale 14 (ds 14) was administered upon admission to the hospital. Results: After controlling for demographic and clinical confounders, non–type D patients reported statistically significant higher frequencies of smoking cessation when compared with the type D group. In addition, the presence of this psychological factor anticipates significantly the onset of smoking during adolescence. Furthermore, current type D smokers had a higher incidence of cardiovascular events during long‐term follow‐up. Conclusions: Type D personality and smoking status increase the risk of cardiac events. An emotionally stressed personality and persistence of smoking after the first cardiac event, and mostly their mutual influence, indicate a population at high cardiovascular risk.